The - Briggs, Adrian (Oxford University Press, 2002)
This new addition to the Clarendon Law Series offers a much needed introduction to a complex subject. The Conflict of Laws addresses the jurisdiction of English Courts (and whether their judgments are enforced and recognised overseas) and the effect of foreign judgments in England (whether these are recognised and enforced here). It also looks at the principles of choice of law for cases with an international element which are adjudicated in English courts